Inverse Problems for Sturm-Liouville-Type Differential Equation With the Fixed Delay Under Discontinuity Conditions - Bošković, Milica; Vladičić, Vladimir (Sarajevo Journal of Mathematics, 2022)
In this manuscript, we consider boundary value problems for the equation with the fixed delay and transmission conditions on π2. We study the case when all parameters in transmission conditions are known. We will prove theorem of uniqueness from two spectra, first with Dirichlet-Dirichlet boundary conditions and second with Dirichlet-Neumann boundary condition. Also, we implicitly give the algorithm for determining the potential from these two spectra.